The Investigation of Meta-Affective Differences Between Gender in Vocational High Schools During Learning Science - Rusyati, Lilit; Rustaman, Nuryani Y.; Widodo, Ari; Ha, Minsu (Journal of Technical Education and Training, 2022)
The presence of feelings has an impact on science learning, which involves not only studying theory but also practising. Making groups in learning sometimes do not pay attention to the ability to recognize and regulate the feelings of male and female students. This survey research is to investigate meta-affective based on students’ experiences in learning science. The research instrument is a questionnaire compiled based on the Awareness Dimension (10 statements) and Regulation Dimension (7 statements) with the level of response, namely frequency (scale 1-6). The research subjects involved were 160 students in Vocational High Schools, with 80 males and 80 females. The results show a comparison between male and female students based on average responses. Students who were female had higher average response scores than students who were male in both the tests of affective awareness and affective control. With the exception of one item, both versions have the same score. The items are MATS-12 "If I get angry with myself when I do not understand a topic, I notice that feeling" on affective awareness and MATS-10 "If I feel angry when I am not successful, I try to control it". These results conclude that noticing angry feelings and controlling them is the same ability between male and female students. This suggests that, except for rage, which can be recognized and managed by both sexes of students, female students are better able to recognize and manage their emotions.